Analysis of Feminism in The ‘Moxie’ Movie - Natasya Natasya (CV. Ulil Albab Corp, 2022)
This research is entitled “Feminism Seen through the Main Character in ‘Moxie’ Movie”. This study talked about the feminism values that seen through in the main character in moxie movie. This study based on how single human being wants to get treated equally to express themselves in every aspect in their life for example in gender. The two purposes in this study were to find out the kind of feminism by character in ‘moxie’ movie script and to know the factors causing the appearance of feminism in the movie. The descriptive qualitative study applied in this study and analyzed by using Tong theory (2009). The data in this study was collected by using observation method and note-taking technique. To present the analysis, this study applied the informal methods and the result of the analysis was presented in the form of words.